SAD-1 kinase controls presynaptic phase separation by relieving SYD-2/Liprin-α autoinhibition. - Nathan A McDonald; Li Tao; Meng-Qiu Dong; Kang Shen (PLoS Biology, 2023)
Neuronal development orchestrates the formation of an enormous number of synapses that connect the nervous system. In developing presynapses, the core active zone structure has been found to assemble through liquid-liquid phase separation. Here, we find that the phase separation of Caenorhabditis elegans SYD-2/Liprin-α, a key active zone scaffold, is controlled by phosphorylation. We identify the SAD-1 kinase as a regulator of SYD-2 phase separation and determine presynaptic assembly is impaired in sad-1 mutants and increased by overactivation of SAD-1. Using phosphoproteomics, we find SAD-1 phosphorylates SYD-2 on 3 sites that are critical to activate phase separation. Mechanistically, SAD-1 phosphorylation relieves a binding interaction between 2 folded domains in SYD-2 that inhibits phase separation by an intrinsically disordered region (IDR). We find synaptic cell adhesion molecules localize SAD-1 to nascent synapses upstream of active zone formation. We conclude that SAD-1 phosphorylates SYD-2 at developing synapses, activating its phase separation and active zone assembly.